Lessons on general linguistic subjects in grades 6-7: intensifying the informational forming component (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The paper is devoted to the problem of applying linguistic studies in the practice of giving introductory lessons of Ukrainian. Teacher’s examination of results of ethno-, sociolinguistica and linguistic research itself will intensify informational forming component of introductory lessons of Ukrainian and that will be conductive to increase of pupils’ learning activity.
Keywords: language; lessons on general linguistic subjects; results of linguistic research; informational forming component